PENERAPAN TEKNOLOGI SEDERHANA PEMANFAATAN LIMBAH KULIT PISANG SEBAGAI ENERGI ALTERNATIF PADA BATTERAI MELALUI PEMBELAJARAN IPAS DI SEKOLAH DASAR - Hendri Marhadi; Jaya Adi Putrai; Neni Hermita; Zetra Hainul Putra; Jesi Alexander Alim; Erlisnawati; Mahmud Alpusari; Risnawati Risnawati (STKIP Subang, 2026)
IPAS learning in elementary schools is still tend to be conducted conventionally, resulting in suboptimal student involvement in the learning process. This condition causes students to have difficulty understanding the concept of energy and energy transformation, which are abstract in nature. This community service activity aims to apply simple technology using banana peel waste as an alternative energy source in batteries thru STEM-based IPAS learning in elementary schools. The implementation method of the activity consists of stages such as Focus Group Discussion (FGD), socialization, learning application, as well as evaluation and mentoring. At the implementation stage, students directly practice making a simple battery from banana peels until they successfully light up an LED. Evaluation is conducted using pretests and posttests to determine the improvement in students' understanding. The results of the activity show that there was an increase in student understanding across all indicators, with an overall N-Gain value of 0.69, categorized as moderate. Simple practice-based learning can enhance student activity, learning motivation, and understanding of the concept of electrical energy and the utilization of organic waste. In addition, the application of STEM-based learning can also train students' critical thinking skills, creativity, collaboration, and environmental awareness. Thus, the utilization of banana peel waste as an alternative energy source can become an innovative contextual and interactive learning approach in elementary school IPAS education.